Interpretasi Hakim Mengenai Unsur-Unsur Dakwaan Subsidaritas dalam Pasal 2 Juncto Pasal 3 Undang-Undang Pemberantasan Tindak Pidana Korupsi Perspektif Sociological Jurisprudence dan Al Qowaidh Al Fiqhiyyah (Studi Lapangan Pengadilan Tindak Pidana Korupsi Surabaya): The Judge's Interpretation of the Elements of Subsidiary Charges under Article 2 Juncto Article 3 of the Law on Eradication of Corruption Crimes from the Perspective of Sociological Jurisprudence and Al Qowaidh Al Fiqhiyyah (Field Stu - Fatihul Ihsan (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2026)
Legal inconsistency between Article 2 and Article 3 of the Corruption Eradication Law has led to clear sentencing disparities as reflected in the provisions of these articles. Judges’ considerations serve as the fundamental basis for arguments in deciding cases; if such arguments are inaccurate, the resulting decisions may be perceived as incorrect and unjust by society. This study examines the differences in judges’ interpretations in understanding the elements of subsidiary indictments within the Corruption Eradication Law. It employs a qualitative approach, involving interviews with Ad Hoc Judges of the Corruption Court in Surabaya. The focus of this research includes: (1) the relevance of Supreme Court Regulation (PERMA) No. 1 of 2020 in judicial decision-making; (2) the perspective of Sociological Jurisprudence on judges’ interpretations of the elements of subsidiary indictments under Article 2 in conjunction with Article 3 of the Corruption Eradication Law; and (3) the perspective of the Islamic legal maxim ad-dhorurotu tuqoddaru biqodriha on judges’ interpretations of the elements of subsidiary indictments under the same provisions. This research is categorized as empirical legal research or field research, utilizing two approaches: a statutory approach and a direct field approach. Data analysis was conducted through several stages, including data reduction, data presentation, and conclusion drawing. The results of this study indicate that Supreme Court Regulation No. 1 of 2020 remains relevant and plays a significant role in guiding judges in deciding corruption cases under Article 2 in conjunction with Article 3 of the Corruption Eradication Law, as well as in minimizing sentencing disparities, except in splitsing cases involving different roles of perpetrators. Judges’ interpretations of subsidiary indictments reflect a Sociological Jurisprudence approach that accommodates societal values of justice without neglecting the strict nature of criminal law, while still relying on trial facts and statutory provisions. From the perspective of the Islamic legal maxim ad-dhorurotu tuqoddaru biqodriha, corruption remains a prohibited act, and emergency conditions do not eliminate its unlawful nature nor the criminal liability of the perpetrator Inkonsistensi Hukum pada pasal 2 dan pasal 3 Undang – undang Pemberantasan Tindak Pidana Korupsi menyebabkan Disparitas pemidanaan yang jelas pada bunyi pasal. Pertimbangan Hakim adalah dasar Argumen dalam memutus perkara, jika Argumen tidak tepat maka putusan bisa dianggap tidak benar dan tidak adil oleh masyarakat. Penelitian ini mengkaji tentang perbedaan penafsiran hakim dalam memaknai Unsur –unsur dakwaan subsidairitas pada Undang –undangTindak Pidana Korupsi. Melalui pendekatan Kualitatif, yakni dengan wawancara kepada Hakim Adhoc Pengadilan Tindak Pidana Korupsi Surabaya. Fokus Penelitian ini diantaranya : (1) Bagaimana Relevansi PERMA No. 1 Tahun 2020 terhadap pengambilan Putusan oleh Hakim?, (2)Bagaimana Pandangan Sosial Jurisprudence terhadap Interpretasi Hakim mengenai Unsur – unsur dakwaan Subsidaritas dalam Pasal 2 Juncto Pasal 3 Undang –undang Pemberantasan Tindak Pidana Korupsi ?,(3) Bagaimana Pandangan Kaidah Fikih ad Dhorurotu Tuqoddaru Bidoqriha terhadap Interpretasi Hakim mengenai Unsur – unsur dakwaan Subsidaritas dalam Pasal 2 Juncto Pasal 3 Undang – undang Pemberantasan Tindak Pidana Korupsi ? Jenis penelitian ini termasukdalam kategori penelitian hukum Empiris atau penelitian lapangan, dengan menggunakan dua pendekatan, yakni pendekatan perundang – undangan dan pendekatan langsung di lapangan. Proses analisis data dilakukan melalui beberapa tahap, meliputi reduksi data, penyajian data,serta penarikan kesimpulan. Hasil Penelitian ini dapat Disimpulkan : Bahwa PERMA no 1 tahun 2020 masih relevan dan berperan penting dalam memandu hakim menjatuhkan putusan perkara tindak pidana korupsi pasal 2 jo pasal 3 UU TIpikor serta meminimalisir disparitas pemidanaan, kecuali dalam perkara Splitsing dengan perbedaan peran pelaku. Interpretasi hakim terhadap dakwaan subsidairitas mencerminkan pendeketakan Sociological Juriprudence yang mengakomodasi nilai keadilan masyarakat tanpa mengesampingkan sifat ketat hukum pidana. Dengan tetap bertumpu pada fakta persidangan dan ketentuan perundang – undangan. Dari perspektif kaidah fikih adDhorurotu tuqoddaru Biqodriha, korupsi tetap merupakan perbuatan terlarang dan kondisi darurat tidak menghapuskan sifat melawan hukum maupun pertanggungjawaban pidana pelaku.